Simultaneous solidification of two catalyst wastes and their effect on the early stages of cement hydration - Melchert, Maura B. M. [UNESP]; Viana, Marcelo M. [UNESP]; Lemos, Mariana S.; Dweck, Jo; Buechler, Pedro M. [UNESP] (Springer, 2011)
Two catalyst wastes (RNi and RAI) from polyol production were considered as hazardous, due to their respective high concentration of nickel and aluminum contents. This article presents the study, done to avoid environmental impacts, of the simultaneous solidification/stabilization of both catalyst wastes with type II Portland cement (CP) by non-conventional differential thermal analysis (NCDTA). This technique allows one to monitor the initial stages of cement hydration to evaluate the accelerating and/or retarding effects on the process due to the presence of the wastes and to identify the steps where the changes occur. Pastes with water/cement ratio equal to 0.5 were prepared, into which different amounts of each waste were added. NCDTA has the same basic principle of Differential Thermal Analysis (DTA), but differs in the fact that there is no external heating or cooling system as in the case of DTA. The thermal effects of the cement paste hydration with and without waste presence were evaluated from the energy released during the process in real time by acquiring the temperature data of the sample and reference using thermistors with 0.03 A degrees C resolution, coupled to an analog-digital interface. In the early stages of cement hydration retarding and accelerating effects occur, respectively due to RNi and RAl presence, with significant thermal effects. During the simultaneous use of the two waste catalysts for their stabilization process by solidification in cement, there is a synergic resulting effect, which allows better hydration operating conditions than when each waste is solidified separately. Thermogravimetric (TG) and derivative thermogravimetric analysis (DTG) of 4 and 24 h pastes allow a quantitative information about the main cement hydrated phases and confirm the same accelerating or retarding effects due to the presence of wastes indicated from respective NCDTA curves.
Keywords: Waste catalysts; Solidification; Stabilization; Cement; NCDTA; TG